2018
DOI: 10.1093/ofid/ofy338
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis: The Heart of the Diagnosis

Abstract: Toxoplasma gondii is a common parasite that infects warm-blooded animals, including humans, and is a foodborne pathogen. We report a case of acute toxoplasmosis in a 76-year-old man after ingestion of the undercooked heart of a white-tailed deer (Odocoileus virginianus) in Tennessee. The patient’s adult grandson, who also consumed part of the heart, became ill with nearly identical symptoms, though he did not seek medical care. This case highlights important public health concerns about deer-to-human transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…22.2% of myocardiopathy patients suffer from cardiovascular patients, also they have toxoplasmosis. This report agreed with (England, J. H. et al, 2019), who reported that 26% with cardiovascular disease and they complaining myocardiopathy with Toxoplasmosis (8) (9) . Cardiomyopathy is the disease of the cardiac muscles.…”
Section: Discussionsupporting
confidence: 91%
“…22.2% of myocardiopathy patients suffer from cardiovascular patients, also they have toxoplasmosis. This report agreed with (England, J. H. et al, 2019), who reported that 26% with cardiovascular disease and they complaining myocardiopathy with Toxoplasmosis (8) (9) . Cardiomyopathy is the disease of the cardiac muscles.…”
Section: Discussionsupporting
confidence: 91%
“…Cases of acute toxoplasmosis and two recent outbreaks among hunters in Wisconsin and Illinois, USA, have already been linked to the consumption of insufficiently heated or raw game [ 15 , 16 , 17 , 18 , 19 , 20 , 42 ]. In order to reliably assess the risk of human T. gondii infection from the consumption of game, information on the occurrence of T. gondii in the most frequently consumed game species is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, consumption of raw or undercooked meat, including game, was linked to a higher risk of T. gondii infection in Europe [ 13 , 14 ]. Multiple known cases of acute toxoplasmosis have been associated with the consumption of raw or insufficiently heated deer and wild boar meat [ 15 , 16 , 17 , 18 , 19 , 20 ]. Handling raw meat or the carcasses of wild animals could also result in potential smear infections [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the USA, a strain of T. gondii most commonly found in North American wildlife was recently shown to be responsible for 12 atypical cases of toxoplasmosis [112]. Indeed, epidemiological studies and several outbreaks have identified consumption of raw or undercooked game as a potential source of acute toxoplasmosis [107,[112][113][114][115][116] even in pregnant women [109,114]. Additionally, also handling of game carcasses was shown to be a possible source of acquired ocular toxoplasmosis in previously healthy hunters [115,117].…”
Section: Public Health Aspectsmentioning
confidence: 99%